2022
DOI: 10.1093/mnras/stac1708
|View full text |Cite
|
Sign up to set email alerts
|

Morphological decomposition of TNG50 galaxies: methodology and catalogue

Abstract: We present mordor (MORphological DecOmposeR, a new algorithm for structural decomposition of simulated galaxies based on stellar kinematics. The code measures the properties of up to five structural components (a thin/cold and a thick/warm disc, a classical and a secular bulge, and a spherical stellar halo), and determines the properties of a stellar bar (if present). A comparison with other algorithms presented in the literature yields overall good agreement, with mordor displaying a higher flexibility in cor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…Overall, we see strong clues that the Hubble sequence is well developed by z = 1.5. The current generation of cosmological hydrodynamic simulations, such as TNG50 (the highestresolution run of the IllustrisTNG suite), do predict a significant proportion of disks in star-forming galaxies at high redshifts, for instance ∼30% at z ; 3 and ∼50% at z ; 2 for M  10 9.5 M e (Pillepich et al 2019, see their Figure 9), and moreover predict a population of well-developed spirals with bulges at z = 2 visible in rest-frame optical (although this may be sensitive to decomposition morphology; see Zana et al 2022). As additional JWST imaging data becomes available over wider fields, we will be better able to empirically confirm (or challenge) these predictions.…”
Section: Prevalence Of Disks Bulges and Spiral Structurementioning
confidence: 96%
“…Overall, we see strong clues that the Hubble sequence is well developed by z = 1.5. The current generation of cosmological hydrodynamic simulations, such as TNG50 (the highestresolution run of the IllustrisTNG suite), do predict a significant proportion of disks in star-forming galaxies at high redshifts, for instance ∼30% at z ; 3 and ∼50% at z ; 2 for M  10 9.5 M e (Pillepich et al 2019, see their Figure 9), and moreover predict a population of well-developed spirals with bulges at z = 2 visible in rest-frame optical (although this may be sensitive to decomposition morphology; see Zana et al 2022). As additional JWST imaging data becomes available over wider fields, we will be better able to empirically confirm (or challenge) these predictions.…”
Section: Prevalence Of Disks Bulges and Spiral Structurementioning
confidence: 96%
“…The lack of barred galaxies remains clear for M * < 10 10.5 M in TNG50 even when comparing with other observational bar fraction estimates (Oh et al 2012). Note that the measured bar fraction in TNG50 at M * < 10 10.5 M is however higher in Zana et al (2022) than in Roshan et al (2021), but still not quite as high as in Oh et al (2012). Note that Masters et al (2012); Melvin et al (2014) found even smaller observational bar fractions at small masses, as well as an increasing bar fraction with mass in contradistinction with various other studies (Díaz-García et al 2016;Consolandi 2016).…”
Section: Introductionmentioning
confidence: 55%
“…Examining luminous face-on spiral galaxies from the COSMOS survey, Sheth et al (2008) found that the fraction of barred galaxies is highly dependent on the redshift, sharply increasing from ∼20% at z ∼ 0.84 to ∼65% in the local Universe, which was confirmed in cosmological simulations (e.g. Cavanagh et al 2022;Zana et al 2022). Such a high difference cannot be explained by the flybys alone.…”
mentioning
confidence: 85%
“…Using a tool for the structural decomposition of galaxies based on stellar kinematics (e.g. MORDOR algorithm, Zana et al, 2022) could help us estimate the amount of transferred mass since the majority of particles associated with the bar would be flagged as a pseudo-bulge component. A strong bar in simulation B30, which accounts for roughly 20% of the total disc mass (or around 30% of the inner disc, where R < 15 kpc), captures up to 6% of the bulge particles.…”
Section: The Effect On Spherical Componentsmentioning
confidence: 99%